Runoff, Soil and Nutrient Losses from Major Agricultural Land-use Practices in the Lake Victoria Basin, Uganda - Magunda, M. K. (LVFO, 2001)
Soil degradation by water erosion is recognized lo be a major agricultural and environmental problem in the Lake Victoria basin. The objective of this study was to quantify runoff, soil and nutrient losses from major agricultural land-use types (Annual crops. banana. coffee and degraded rangelands) and assess the efficiency of contour bunds 'in reducing those losses in two selected micro-catchments of the Luke Victoria Basin. The experiment was conducted 011 13 runoff plots of 15 hy lO In. Each land-usc type was replicated three times, except banana. Con lour bunds were hand constructed two years after establishment of runoff plots. at 20-01 spacing interval. Before the establishment of contour bunds, the average annual runoff ranged between 315.47 and 2438.92 01' h::r'/yr. with relatively higher amount of rainfall water 10$s on rangelands compared to banana and coffee (p=O.022), The avarage annual soil loss ranged from 27.7 to g6.7 t/ha/yr, with higher soil [OS5 on annuals compared to banana and coffee (p=O.038). Seasonal soil losses contributed tor more than 75% of the annual losses for all agricultural land-use. while seasonal runoff contributed the same proportion only for banana and rangelands (p<O.05). Eroded sediments had relatively high nutrient concentrations than the remaining soils, and varied with land-Lise and lor seasons (p<O.05), The amount ofN, P, K and organic matter (OM) lost through erosion was relatively high. and varied with seasons (p<O (5) The establishment of contour bunds increased OM. Ca and Na content in eroded sediments. while it decreased total OM. TN losses for all land-use types except on rangelands where they increased one year after. These exports from agricultural land play a major role in the nutrient enrichment of rivers and open bodies
Keywords: Farming systems; Land degradation; Land Productivity; Soil degradation; Soil quality